THE INFLUENCE OF ATTACHMENT EDUCATION AND INFANT POSITIONING ON BREASTFEEDING SUCCESS - Heni Purwaningsih; Istiqomah Istiqomah (Jurnal SMART Keperawatan, 2025)
Background: Breastfeeding is essential for the physical and emotional health of both mother and baby. Proper breastfeeding techniques, including correct position and attachment, enhance bonding and provide optimal nutrition for the baby. Incorrect techniques can lead to issues like breast pain, sore nipples, and reduced milk production. Objective: to determine the effect of education on attachment and position of the baby on the success of breastfeeding. Method: The research used a pre-experimental approach with the One-Group Pretest-Posttest Design. The population of mothers who had just given birth at PKU Muhammadiyah Hospital Surakarta. The number of samples was 21 breastfeeding mothers using purposive sampling. The breastfeeding success instrument used the LATCH score checklist and educational media used props (phantoms and leaflets). Data Analysis used the Wilcoxon Signed Rank Test. Results: showed that most mothers were aged 26-35 years, had a high school education and were working mothers. Before being given education, most mothers after giving had a successful breastfeeding process that was less effective. After being given health education, it was known that most mothers had a successful breastfeeding process that was effective. That education on the position and attachment of the baby affected the success of the breastfeeding process p-value 0,000. Conclusion: There is an effect of education on the position and attachment on the success of breastfeeding.